A new type of dendritic [60]fullerene-metallo-tetraphenylporphyrin diads (M = Zn, Co) - Kovács, Christian; Hirsch, Andreas (European Journal of Organic Chemistry, 2006)
The synthesis of unsymmetrical malonates 19-23 terminated by a metallo-tetraphenylporphyrin (M = Zn, Co, Co ) and by Newkome-type amide dendrons of generation two and three is reported. Cyclopropanation of C with the second-generation dendrons 20 and 21 leads to the formation of fullerene monoadducts 24 and 25, representing a new type of dendritic diads. The establishment of Co in the oxidation sates of +II and +III was achieved by the treatment with Na SO or with O in the presence of CN and SCN, respectively, leading to the paramagnetic complex 26 and the diamagnetic axially coordinated complexes 27. Deprotection of the tert-butyl groups terminating the dendritic branch of the diads 24 and 25 generates the corresponding water-soluble systems 28 and 29. Due to their amphiphilic character micellar aggregates are formed in water. DOSY NMR measurements showed that the aggregates consisting of 28 have an average diameter of approximately 7 nm in a buffered DO solution (pH = 7.2). © Wiley-VCH Verlag GmbH & Co. KGaA, 2006.